THE IMPLEMENTATION OF DEMONSTRATION METHOD TO IMPROVE STUDENTS’ SPEAKING SKILS IN PROCEDURE TEXT - Miftahul Jannah; Nurdevi Bte Abdul; Sitti Maryam Hamid (English Language Teaching Methodology, 2021)
Speaking is one of the active skills that have to be mastered by students. One of the texts that have to learn by students is procedure text. Procedure text is a text that contains information that includes instruction, procedure or steps or ways that show how something is done. Due to the characteristic the use of demonstration method is an interesting choice. This research aimed to improving students’ speaking skills in procedure text at the twelfth grade students of SMA Muhammadiyah 5 Makassar using demonstration method. The researchers used pre-experimental research by quantitative method where the data gained from the oral test. The population of the research was the twelfth grade of SMA Muhammadiyah 5 Makassar in the academic year 2020/2021. The sample was taken by using purposive sampling technique there were 20 students of 151 students. The result presented that the students’ pre-test mean score in form of vocabulary was 39 to be 78 in post-test with 100% improvement. Then, the mean score in form of pronunciation was 39 in the pre-test to be 77.5 in the post test with 98.72% improvement. The t-test analysis presented that by applying 0.05 level of significant with the 19 degree freedom (df=20-1), t-test in the form of vocabulary and pronunciation higher than t-table which were 22.16>2.093 and 21.43>2.093. It means that demonstration method has significant effect toward students’ speaking skills in procedure text in the form of vocabulary and pronunciation.